2018
DOI: 10.13164/re.2018.0431
|View full text |Cite
|
Sign up to set email alerts
|

Seabed-Rock-Layer Electromagnetic Communication Channel Model with Low Path Loss Based on Evanescent Wave

Abstract: The main limitation of the development of underwater wireless electromagnetic communication is severe attenuation introduced by the seawater characteristics of high permittivity and high conductivity. Fortunately, in previous studies, it was found through experiments that the loss between two underwater antennas near seawater surface or seabed is much smaller than the higher order severe attenuation for the line of sight (LOS) path in seawater. But no one has given reasonable explanation for this phenomenon. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…e phenomenon is depicted in Figure 1. Similarly, a wave propagation modeling at the seawater-seabed interface can be monitored for the deeply submerged transceiver [23]. e sudden change in conductivity at the seawater-air interface instead of the seawater-seabed interface distinguishes the two events.…”
Section: Em Modeling For Conductive Mediummentioning
confidence: 99%
“…e phenomenon is depicted in Figure 1. Similarly, a wave propagation modeling at the seawater-seabed interface can be monitored for the deeply submerged transceiver [23]. e sudden change in conductivity at the seawater-air interface instead of the seawater-seabed interface distinguishes the two events.…”
Section: Em Modeling For Conductive Mediummentioning
confidence: 99%
“…Another study at higher frequencies reported some feasibility of using EMW in underwater systems using the unlicensed the industrial, scientific, and medical (ISM) frequency bands, which are 6.7 MHz, 433 MHz and 2.4 GHz (Abdou et al, 2011). Investigations on alternative underwater EMW propagation other than LOS are also reported, such as in Nie et al (2018), where a sea-rock-layer propagation model is analyzed by simulation, using narrowband signal up to 150 kHz. The proposed model marked a 1/20 path loss compared to the LOS configuration.…”
Section: Introductionmentioning
confidence: 99%